2018
DOI: 10.1111/aas.13249
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal tube cuff pressure changes during manual cuff pressure control manoeuvres: An in‐vitro assessment

Abstract: Routine manual cuff pressure control manoeuvres in ETT cuffs result in considerable cuff pressure drops. This may have an impact on silent aspiration of pharyngeal contents passing along the cuff into the lower airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Furthermore, there was an expression of concern for the cause of leaks by one respondent, which has been demonstrated in the literature. 27,28 For example, cuff pressure drops can be experienced from the initial connection or disconnection of the manometer to the pilot balloon and less frequently by the pressure gauge of the manometer. 27 However, correct use of cuff manometers with three-way valves or the use of continuous monitoring techniques have been described to avoid this complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there was an expression of concern for the cause of leaks by one respondent, which has been demonstrated in the literature. 27,28 For example, cuff pressure drops can be experienced from the initial connection or disconnection of the manometer to the pilot balloon and less frequently by the pressure gauge of the manometer. 27 However, correct use of cuff manometers with three-way valves or the use of continuous monitoring techniques have been described to avoid this complication.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 For example, cuff pressure drops can be experienced from the initial connection or disconnection of the manometer to the pilot balloon and less frequently by the pressure gauge of the manometer. 27 However, correct use of cuff manometers with three-way valves or the use of continuous monitoring techniques have been described to avoid this complication. 29,30 Access to and the routine use of cuff manometers in Australian and New Zealand institutions is not mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, in patients with automated P cuff adjustment but not in patients from routine care group, we used a three-way stopcock. Of note, direct connection of the manometer to the endotracheal tube may be source of air leakage [27]. The use of the three-way stopcock may have limited the air leakage by connecting the manometer before opening the dedicated outlet.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study, as well as, other sever studies has demonstrated that this unreliable technique puts patients at the risk of unnecessary high intra-cuff pressure with subsequent laryngotracheal complication. [19][20][21][22][23]…”
Section: Regulation Of Ett Cuff Pressure 41 Estimation Of Cuff Pressure By Pilot Balloon Palpationmentioning
confidence: 99%